Electric Current Field‐Assisted Inclusions Capture by Bubbles in Molten Steel. Issue 7 (16th April 2020) - Yan, Longge; Zhang, Xinfang
Abstract : Electric current is used to assist bubbles in removing inclusions from molten steel. Generally, large‐size bubbles do not effectively remove inclusions but instead convectively agitate the molten steel. The results show that the number of inclusions in the sample is reduced by 45% after the large‐size bubbles are coupled with the pulsed current, whereas the amount of inclusions in the sample treated only with large‐size bubbles does not change much. Numerical calculation reveals that electric current induces a force acting on the inclusion as the inclusion is close to a bubble. According to the nature of the force, there are three different effects, i.e., repulsion, attraction, and driven. The electric free energy change is calculated as well when an inclusion is captured by a bubble. Electric current causes a longer contact time and a shorter induction time between inclusions and bubbles, thus improving the collision and attachment probability and decreasing the detachment probability. As a result, inclusions are more easily captured by bubbles. Abstract : The purification region of bubble coupling current is larger than that of pure current in removing inclusions. Moreover, the inclusion number treated by bubble coupling current reduces by about 45% compared with that treated only by bubbles. According to the model in this work, the current‐induced force acting on inclusion makes Al2 O3 inclusions more easy to be captured by bubbles.